The impact of microbial keratitis on quality of life in Uganda. Issue 1 (23rd December 2019) - Arunga, Simon; Wiafe, Geoffrey; Habtamu, Esmael; Onyango, John; Gichuhi, Stephen; Leck, Astrid; Macleod, David; Hu, Victor; Burton, Matthew
Abstract : Background: Microbial keratitis (MK) is a frequent cause of sight loss in sub-Saharan Africa. However, no studies have formally measured its impact on quality of life (QoL) in this context. Methods: As part of a nested case–control design for risk factors of MK, we recruited patients presenting with MK at two eye units in Southern Uganda between December 2016 and March 2018 and unaffected individuals, individually matched for sex, age and location. QoL was measured using WHO Health-Related and Vision-Related QoL tools (at presentation and 3 months after start of treatment in cases). Mean QoL scores for both groups were compared. Factors associated with QoL among the cases were analysed in a linear regression model. Results: 215 case-controls pairs were enrolled. The presentation QoL scores for the cases ranged from 20 to 65 points. The lowest QoL was visual symptom domain; mean 20.7 (95% CI 18.8 to 22.7) and the highest was psychosocial domain; mean 65.6 (95% CI 62.5 to 68.8). At 3 months, QoL scores for the patients ranged from 80 to 90 points while scores for the controls ranged from 90 to 100. The mean QoL scores of the cases were lower than controls across all domains. Determinants of QoL among the cases at 3 months included visual acuity at 3 months and history of eye loss. Conclusion: MK severely reduces QoL in the acute phase. With treatment and healing, QoL subsequently improves. Despite this improvement, QoL of someone affected by MK (even with normal vision) remains lower than unaffected controls.